An algorithmic approach to single‐probe Cherenkov removal in pulsed x‐ray beams. Issue 4 (14th February 2019) - Archer, James; Madden, Levi; Li, Enbang; Wilkinson, Dean; Rosenfeld, Anatoly B.
Abstract : Purpose: The removal of Cherenkov light in an optical dosimetry system is an important process to ensure accurate dosimetry without compromising spatial resolution. Many solutions have been presented in the literature, each with advantages and disadvantages. We present a methodology to remove Cherenkov light from a scintillator fiber optic dosimeter in a pulsed megavoltage x‐ray beam using the temporal waveform across the pulse. Methods: A sample waveform of Cherenkov light can be measured by exposing only the fiber to the beam. By assuming that the Cherenkov waveform closely matches the intensity of incident radiation, this waveform can be convoluted with the instantaneous scintillation response function to generate an expected scintillation signal. By finding the least‐squares fit between these two functions and the experimental data, the estimated Cherenkov contribution can be subtracted off the net signal. This can be applied for arbitrarily complex Cherenkov waveforms (within the 2 ns timing resolution of the data acquisition), and in fact, the results suggest more fluctuations in the waveforms provide a better fit to data. Results: Four beam profiles for different field sizes and energies were found with this method. They closely matched references data measured with ionization chamber with average differences across the beam no more than 4%. Noisy waveforms are assumed to be the primary cause of differences between the analyzed scintillator and IC results. We propose methods for improving the results and optimizing the data acquisition and analysis processes. Conclusions: These results demonstrate that it is possible and effective with a single probe to use function fitting of expected data to experimental to remove a complicated Cherenkov signal from the net light signal in pulsed‐beam optical dosimetry.